Calcareous plankton and geochemistry from the ODP site 1209B in the NW Pacific Ocean (Shatsky Rise): new data to interpret calcite dissolution and paleoproductivity changes of the last 450 ka. - Bordiga M.; Beaufort L.; Cobianchi M.; Lupi C.; Mancin N.; Pelosi N.; Sprovieri M.; LUCIANI, Valeria (Palaeogeography, Palaeoclimatology, Palaeoecology, 2013)
The high-resolution, multi-proxy investigation of microfossil and isotopic data from Shatsky Rise (ODP Site 1209B, NW Pacific Ocean) is presented to evaluate the potential of calcareous nannofossil assemblages as dissolution and paleoproductivity proxies over the last 450 ka. To identify the best nannofossil index to evaluate dissolution (in particular, under polarized light microscope), we calculate and compare the different nannofossil and planktonic foraminiferal dissolution-indices from our original dataset. The results demonstrate that the most reliable and reproducible nannofossil dissolution index is the Nannofossil Dissolution Index (NDI) proposed by Marino et al. (2009), particularly for records prior to 250 ka. The NDI data from the studied Site 1209B represent evidence of preservation maxima mainly during deglaciations, whereas dissolution peaks are recorded at the onset of glacial phases or during severe interglacials. These fluctuations are demonstrated to be basin-wide features in the Pacific. The synchronous timing in the fluctuations of the preservation indices, which consistently lagged behind the oxygen isotope cycles, clearly demonstrates the basin-wide changes in the ocean chemistry during the glacial–interglacial transitions. The Mid-Brunhes Dissolution Event, which was recorded in the Western Pacific at depths below the lysocline at the Marine Isotope Stage (MIS) 11, is not detectable at our relatively shallower site. At the studied site, the intervals of high productivity generally coincide with the time of good preservation and light carbon-isotope values and vice versa. Therefore, carbonate undersaturation and changes in ocean chemistry (carbonate ion concentration) rather than the variations in the organic carbon flux appear to have controlled the pattern of CaCO3 preservation. In addition to the characterization of the dissolution proxies, changes in the calcareous nannofossil assemblages were used to evaluate the primary productivity fluctuations at the mid-latitudes of the NW Pacific ...